Robotic Resection of a Superior Sulcus Neurogenic Tumor. Issue 2 (March 2015) - Nguyen, Duy C.; Garagozlo, Cameron; Moslemi, Mohammad; Rawashdeh, Badi; Meyer, Mark; Tempesta, Barbara J.; Poston, Robert; Gharagozloo, Farid
Neurogenic tumors do not often occur in the superior sulcus or apex of the chest cavity. Historically, surgical approaches have been dictated by the location of the tumor and its relation to the contiguous structures such as the vertebral bodies, subclavian vessels, and chest wall. Resection is hampered by difficulties with visualization and access within a narrow working space. The shortcomings associated with the traditional surgical approaches create a potential of injury to nearby structures. We present a case of a 43-year-old woman with a superior sulcus neurogenic tumor impinging on the left subclavian vein, who underwent a successful resection without injury to nearby structures. We found that a robotic approach improved visualization of the tumor and nearby structures and increased instrument maneuverability relative to a thoracoscopic approach, along with less pain and recovery time compared with a thoracotomy. This experience suggests that robotics provides a promising alternative for excision of superior sulcus neurogenic tumors, which may reduce associated morbidity.